(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
As a result of the study of concepts, the legality of the definition of open public spaces in the structure of the city, as some subsystem that includes architectural and urban planning, design, engineering and transport elements, is socially oriented and aimed at creating a comfortable, accessible, aesthetically attractive and ecologically safe environment. It has been established that open public spaces are getting a second lease of life today - they are becoming unique centers of attraction and communication, combining aesthetics, functional richness and meeting the social needs of society. Abroad, there is already some experience of creating new or restoring existing open public spaces in order to overcome depressive processes in the urban environment as a legacy of the industrial period. In Ukraine, in turn, where the first manifestations of the change of technological eras in the early 1990s coincided with the establishment of independence and the transition to market relations, the degradation of urban areas was felt quite acutely. In such conditions, there is a need to prevent the further deepening of destructive tendencies in the development of the urban environment. In our country, where urban territories were also destroyed as a result of military operations, their restoration becomes quite urgent and stimulates the search for new approaches to solving this problem. In such conditions, the further formation of open urban spaces is considered as an opportunity to create a subsystem of the primary elements of attraction - open public spaces - multifunctional, with a developed transport and pedestrian infrastructure, aesthetically attractive, ecologically safe, capable of ensuring the activation of the socio-cultural life of citizens.